The Mathematics Learning Media Uses Geogebra on the Basic Material of Linear Equations - Syafitri, Qurnia; Mujib, Mujib; Netriwati, Netriwati; Anwar, Chairul; Wawan, Wawan (Universitas Islam Raden Intan Lampung, INDONESIA, 2018)
This research aims to develop a mathematical learning media using Geogebra software. The research method is used the 4D (Four D Model) research method adopted by Siva sailam Thiagarajan, Dorothy S. Semmel, and Melvyn I. Semmel. namely, define, design, develop. The data collection techniques are used to obtain the data on questionnaires response and interviews. The instruments in this research used questionnaires. The data analysis method using descriptive method. This research is conducted by describing the results of product development in the form of learning media for small groups and large groups with media that has been validated by some validators. The Experts of validation results on the content quality aspect to obtain results with very good criteria and on aspects of the language to obtain results with very good criteria. Trial students VII class in small classes and large classes obtained results with interesting criteria for small groups.